2021
DOI: 10.1016/s2213-2600(20)30330-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nintedanib in patients with systemic sclerosis-associated interstitial lung disease treated with mycophenolate: a subgroup analysis of the SENSCIS trial

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 22 publications
6
93
0
8
Order By: Relevance
“…The benefit of nintedanib over placebo for the annual rate of FVC decline was generally consistent across prespecified subgroups based on age, sex, race, region, ATA status, systemic sclerosis subtype (limited cutaneous vs diffuse cutaneous) and mycophenolate use at baseline [ 43 , 45 ]. The adjusted mean annual rate of FVC decline was − 40.2 mL/year with nintedanib versus − 66.5 mL/year with placebo in patients using mycophenolate at baseline and − 63.9 mL/year versus − 119.3 mL/year in patients not using mycophenolate at baseline [ 45 ].…”
Section: Therapeutic Efficacy Of Nintedanibmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of nintedanib over placebo for the annual rate of FVC decline was generally consistent across prespecified subgroups based on age, sex, race, region, ATA status, systemic sclerosis subtype (limited cutaneous vs diffuse cutaneous) and mycophenolate use at baseline [ 43 , 45 ]. The adjusted mean annual rate of FVC decline was − 40.2 mL/year with nintedanib versus − 66.5 mL/year with placebo in patients using mycophenolate at baseline and − 63.9 mL/year versus − 119.3 mL/year in patients not using mycophenolate at baseline [ 45 ].…”
Section: Therapeutic Efficacy Of Nintedanibmentioning
confidence: 99%
“…The benefit of nintedanib over placebo for the annual rate of FVC decline was generally consistent across prespecified subgroups based on age, sex, race, region, ATA status, systemic sclerosis subtype (limited cutaneous vs diffuse cutaneous) and mycophenolate use at baseline [ 43 , 45 ]. The adjusted mean annual rate of FVC decline was − 40.2 mL/year with nintedanib versus − 66.5 mL/year with placebo in patients using mycophenolate at baseline and − 63.9 mL/year versus − 119.3 mL/year in patients not using mycophenolate at baseline [ 45 ]. Nintedanib also reduced annual FVC decline relative to placebo irrespective of the extent of lung fibrosis [ 46 ] or skin fibrosis [ 47 ] at baseline, FVC as a percentage of predicted value at baseline [ 48 ] or skin fibrosis progression over 52 weeks [ 49 ] (no significant treatment-by-time-by-subgroup interactions).…”
Section: Therapeutic Efficacy Of Nintedanibmentioning
confidence: 99%
“…Although the change in FVC was small (absolute mean decline mean −52.4 mL per year in the nintedanib versus −93.3 mL per year in the placebo group), the mean decline reached a previously shown value of minimal clinically important difference (MCID) in the placebo group, but not in the nintedanib treated population [85]. This beneficial effect on FVC preservation was seen both in MMF and non-MMF cotreated patients, with a numerically lower decline in patients receiving the combination treatment [58]. In the SENSCIS study, Nintedanib showed a safety profile similar to the side effects seen in IPF, particularly affecting the gastrointestinal tract (75.7% of treated patients manifested diarrhea) and requiring dose-adjustment/temporary interruption in almost half of the treated patients [59].…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 75%
“…In the SENSCIS study, Nintedanib showed a safety profile similar to the side effects seen in IPF, particularly affecting the gastrointestinal tract (75.7% of treated patients manifested diarrhea) and requiring dose-adjustment/temporary interruption in almost half of the treated patients [59]. Interestingly, the safety profile was similar in patients receiving or not receiving co-treatment with MMF, which itself carries a gastro-intestinal burden in terms of adverse events [58].…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 91%
“…With regard to trial design and selected patients, it seems reasonable to position nintedanib as first-line for patients with established interstitial lung disease and lung fibrotic pattern both as monotherapy and in combination with mycophenolate mofetil. This has been recently further supported by the subgroup analysis of the SENSCIS trial on SSc-ILD patients who were on concomitant mycophenolate mofetil treatment at baseline where it has been shown that a smaller proportion of patients treated with nintedanib versus placebo (29% versus 40% respectively; odds ratio 0,61 [0,37–1,01]) had a decrease in %predicted FVC ≥ 3.3%, which has been estimated to be the minimal clinically important difference for worsening of FVC in SSc-ILD patients [ 65 ]. Nonetheless, with the hope of a larger effect to counteract interstitial lung disease, the question of the timing of combination will have to be addressed quickly: generalization of upfront combination?…”
Section: Discussionmentioning
confidence: 99%